Efecto del tipo de cubrición y del método de control de la actividad reproductiva en cabras Serranas en la estación de anestro - Valentim, Ramiro (2014)
The main aim of this paper was to study the effects of different breeding - natural mounting vs. artificial insemination - and hormonal control protocols - melatonin + FGA + eCG vs. FGA + eCG - on the reproduction activity of Portuguese Serrana goats in the anestrous season. ln March, 60 adult Serrana goats were randomly divided in two groups: half the goats received a subcutaneous implant of melatonin (18 mg) and the other half got no treatment. Fifty days afterward all goats were treated with an injection of 100 micrograms of PGF2alfa and a vaginal sponge with 20 mg of FGA. Five days later 300 lU of eCG were injected at sponge withdraw. At this time, goats from both groups were randomly divided in two subgroups: half the goats were fertilized by natural mounting and the other half by artificial insemination with frozen semen. Short-term progestagen and eCG treatment was effective in promoting reproduction activity. Melatonin increased the percentage of goats showing estrus but had no significant effect on the percentage of goats presenting high plasmatic levels of progesterone after short-term progestagen and eCG treatment and on fertility. Fertility was significantly higher in Serrana goats fertilized by natural mounting than by artificial insemination with frozen semen.